2012
DOI: 10.1158/0008-5472.can-12-0540
|View full text |Cite|
|
Sign up to set email alerts
|

miRNA-708 Control of CD44+ Prostate Cancer–Initiating Cells

Abstract: Tumor recurrence in prostate cancer has been attributed to the presence of CD44-expressing tumorinitiating cells. In this study, we report that miR-708 is a key negative regulator of this CD44

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
109
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 37 publications
(66 reference statements)
5
109
0
Order By: Relevance
“…Among the 130 miRNAs that showed high expression in our present study, 18 have already been linked to PCa relapse (11)(12)(13)(27)(28)(29)(30). Our results are in agreement with earlier reports that showed that miR-26b, miR-30a-3p, and miR-26a correlate with biochemical failure (12 ).…”
Section: Discussionsupporting
confidence: 93%
“…Among the 130 miRNAs that showed high expression in our present study, 18 have already been linked to PCa relapse (11)(12)(13)(27)(28)(29)(30). Our results are in agreement with earlier reports that showed that miR-26b, miR-30a-3p, and miR-26a correlate with biochemical failure (12 ).…”
Section: Discussionsupporting
confidence: 93%
“…These aberrantly expressed miRNAs play essential roles in the regulation of TIC properties as either TIC suppressors or promoters [20][21][22][23][24] . Moreover, a series of critical signalling pathways involved in the regulation of TIC properties have been uncovered with the identification of the targets of these miRNAs 19,[25][26][27][28] . Importantly, miRNAs are also demonstrated to be promising biomarkers and amenable therapeutic targets 5,19,24 .…”
mentioning
confidence: 99%
“…Interestingly, bioinformatics approaches have predicted onethird of all mammalian genes to be targeted and regulated by miRNAs [25][26][27]. Previous studies have shown that aberrant miRNA expression could impact normal biological processes, resulting in PC initiation and progression [28][29][30]. However, a role of miR-323 in the carcinogenesis of PC has not been studied.…”
Section: Introductionmentioning
confidence: 99%